Morphogenetic classification of the Arctic coastal zone - Nikiforov, S. L.; Pavlidis, Yu. A.; Rachold, Volker; Grigoryev, Mikhail N.; Rivkin, F. M.; Ivanova, N. V.; Koreisha, M. M. (Geo-Marine Letters, 2005)
Arctic coastal evolution is the result of interactions between exogenic and endogenic processes. In the arctic region, this evolution differs from that in other areas of the world’s oceans as a result of interactions between modern wave and ice factors, and the influences of glaciations and large-scale sea level changes in the past. Geologic structure, origin and development determine contemporary relief morphology. Morphology appears to be the most significant relief characteristic, but it is controlled by a set of interactive processes active over long periods. Our approach, in which a multitude of interacting factors are simultaneously analyzed and determined, could be called “morphogenetic”. We consider marine coasts and offshore zones (shelf) as a unit, and providing a general explanation for their evolution. The classification presented here is based upon the general approach given in the Science and Implementation Plan of Arctic Coastal Dynamics (ACD), a project of the International Arctic Science Committee and the International Permafrost Association. Our classification extends beyond the morphological ACD classification to include a morphogenetic classification.